Validation of transmission network and MIBEL data: Deliverable D2.1 - Couto, António (2020)
ABSTRACT: The work presented in this deliverable was developed by LNEG and R&D NESTER as part of the R&D activities of the project OPTIGRID - Methodology for the dynamic line rating analysis and optimal management of power networks. According to the plan activities of Tasks 2.2 and 2.3, the main objective of this deliverable is to present the transmission network and the Iberian electricity market (MIBEL) data gathered and validated to use in each case study. According to the work plan, and as detailed reported in the deliverables from Task 4, three case studies were defined: 1) a region with large distributed wind capacity; 2) a region with large photovoltaic (PV) potential and limited grid capacity.; and 3) market splitting occurrence in MIBEL due to congestion in the interconnections - Figure 1. For these regions, during this project, the high voltage network topology and its electrical characteristics (e.g., cables, resistance, reactance, and susceptance) were collected. The power generation, the loads in the regions under analysis were also obtained. Finally, to address the third case study, the interchange capacity (import and export) available and the bids of the day-ahead and intra-day markets at those hours are also gathered and analysed.